Economic voting in Poland from the perspective of declaration of voters - Tybuchowska-Hartińska, Karolina (Political Preferences, 2013)
The presented analysis related to the Polish specificity of preferences in economic voting and to the dynamics of relations between economic situation and political assessment. The analyzed studies show clearly that voters take into account the economic situation in the country irrespective of supporting a parti- cular party - 'definitely yes' or 'rather yes'(from 75% for Palikot Movement to 79% for PSL). The issue is less important to those respondents who declare elec- toral absenteeism (60,4%). When considering economic program of a candidate or a political party, this is the electorate of the Democratic Left Alliance who definitely pay to it a lot of attention (87,1%). Regardless of declared ideolo- gical views and a party support, the respon- dents pay more attention to the economic program of a candidate/ a party than to the condition of the national economy, and it especially refers to those voters who declare themselves as right wingers (the left +5,7%; the centre +4,3; the right +9%). To sum up, it can be stated that regardless of an adopted criterion (of elec- torates of particular parties or ideological views), about % of the voters declare taking into account the economic situation of the country or the economic program of a candidate / a political party as the factor which has an impact on their votes.